Analisis Perbandingan Biaya Pekerjaan Bekisting Konvensional dan Bekisting Sistem Pada Bangunan Gedung - Oni Guspari; Mafriyal Mafriyal; Rahmi Hidayati; Zulfira Mirani; Picko Wike Amelia (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2022)
Formwork is a temporary concrete mold that holds the concrete from fresh concrete until the concrete reaches sufficient strength. Besides the strength and easy to implementation, the cost of formwork is important thing to consider. In this study, the cost of column, beam and floor slab formwork will be analyzed by comparing the conventional formwork and system formwork on the 1st floor of the IAIN Bukittinggi Laboratory Development Project. This research begins by collecting the main data, namely shop drawings so that the volume and also cost of formwork can be calculated. For analysis conventional formwork using the unit price analysis based on the PUPR Ministerial Regulation 2018, but for price of materials and worker wages based on the Bukittinggi area in 2019. While for system formwork, the rental price based on formwork and scaffolding company, PT. Wijaksana Perkasa Beton. The result of this study indicated that for the 1st floor of the Laboratory Development Project of IAIN Bukittinggi, the cost of system formwork is more expensive than conventional formwork, i.e Rp 381,260,039.29 for system formwork compared to Rp 336,629,299.41 for conventional formwork. The results of this study also have not compared of the speed and ease of carrying out the work between the two types of formwork which will be investigated in the next stage.